A Sublinear Time Algorithm for PageRank Computations - Borgs, Christian; Brautbar, Michael; Chayes, Jennifer; Teng, Shang-Hua (Proceedings of the 9th Workshop on Algorithms and Models for the Web Graph (WAW), 2012)
In a network, identifying all vertices whose PageRank is more than a given threshold value is a basic problem that has arisen in Web and social network analyses. In this paper, we develop a nearly optimal, sublinear time, randomized algorithm for a close variant of this problem. When given a directed network G = (V;E), a threshold value , and a positive constant c > 3, with probability 1 ???? o(1), our algorithm will return a subset S V with the property that S contains all vertices of PageRank at least and no vertex with PageRank less than =c. The running time of our algorithm is always O( n). In addition, our algorithm can be efficiently implemented in various network access models including the Jump and Crawl query model recently studied by [6], making it suitable for dealing with large social and information networks. As part of our analysis, we show that any algorithm for solving this problem must have expected time complexity of ( n ). Thus, our algorithm is optimal up to logarithmic factors. Our algorithm (for identifying vertices with signifi cant PageRank) applies a multi-scale sampling scheme that uses a fast personalized PageRank estimator as its main subroutine. For that, we develop a new local randomized algorithm for approximating personalized PageRank which is more robust than the earlier ones developed by Jeh and Widom [9] and by Andersen, Chung, and Lang [2].